Reconstructing the Concept of Digital-Based Accountability for International Corporations for Unlawful Acts to Achieve Justice from an Indonesian Perspective within the Context of National Legal System Reform - Sutrisno, Andri (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
This research focuses on reconstructing the concept of digital-based accountability for international corporations regarding unlawful acts to achieve justice in Indonesia, particularly within the context of national legal system reform. The rapid development of digital technology has introduced new challenges to Indonesia’s legal system, especially concerning activities of international social media corporations often involving legal violations such as misuse of personal data, illegal content, and privacy breaches. This research adopts a constructivist approach, emphasizing that law is a social construct that must continuously adapt to societal dynamics, including technological advances. The analysis includes a review of relevant national and international regulations and identifies existing legal gaps. The findings reveal the need for updated national regulations that can encompass digital-based international corporations and highlight the importance of enhancing the capacity of law enforcement to understand digital issues. Furthermore, this research recommends international cooperation, increased public digital literacy, and the adoption of business and human rights principles as strategic steps to ensure accountability of international digital corporations in delivering justice for the Indonesian public.